REGULATORY AND METHODOLOGICAL CONTROL OF THE FORMATION PROCESS OF MARKETING STRATEGY ON AGRICULTURAL ENTERPRISES - Гоголь, І. А. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
Ukrainian enterprises faced a number of serious problems during the formation of market relations, at both the macro and micro levels. Nowadays the marketing activities of agricultural enterprises should develop harmoniously and in terms of instability, have a developed survival strategy in the situation that will ensure stable functioning in the market. Currently, there are various kinds of enterprises strategies that were historically modeled during the marketing formation of the enterprises activity, but to develop an own enterprise strategy, one must take into account a large number of factors, dynamic in space and time, particularly regulatory and methodological control of the formation process of marketing strategy. The development of proposals to improve the regulatory framework, which directly influences the marketing strategy formation on agricultural enterprises, is the result of the research. The formation technology of the enterprise marketing strategy was improved during the research. The technology, viewed as a set of interrelated mechanisms, tools and processes, which, unlike the existing ones, anticipates achieving the strategic targets of the entity marketing activity on the basis of selection and choice of alternatives for its implementation. The main impact factors on the implementation of marketing strategies on agricultural enterprises in Khmelnytskyi region as well as regulatory and methodological ways of marketing activity improvement at the macro and micro levels are suggested in the article. Also it was proposed to use the method of determining the impact of macro and micro factors on the marketing activities of agricultural enterprises.